Reinstatement of the Chinese species Cremanthodium gypsophilum (Asteraceae, Senecioneae) - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
Examination of herbarium specimens (including type material) of Cremanthodium principis and C. gypsophilum has revealed that the two species are morphologically very distinct from each other. We therefore reinstate the independent specific status of C. gypsophilum which has been placed in synonymy with C. principis. The latter species is currently known only from the holotype, and all the other specimens previously identified as C. principis should belong to C. gypsophilum.